Travel intentions of travelers in the COVID-19 context: The moderation of fear of COVID-19 - Tu, Ruonan; Park, Sung Kyu; Ding, Yi (Frontiers in Psychology, 2023)
The spread of COVID-19 pandemic in early 2020 has significantly affected the tourism industry. Most current tourism research on emergencies focuses on issues such as the revitalization of the tourism economy. However, research on aspects such as visitor perception has not received sufficient attention, This study contributes to the literature by analyzing the effects of social interactions, multidimensional perceived value, fear of COVID-19, and age on travelers' travel intentions during the COVID-19 pandemic. This study constructs a structural equation model, formulates the corresponding hypotheses, investigates Chinese travelers, and verifies the moderating effect of COVID-19 fear. All of the proposed hypotheses were verified. The three dimensions of perceived value and satisfaction had a significant mediating effect in the relationship between perceived quality and travel intention, and that fear of COVID-19 had a significant moderating effect in the relationship between satisfaction and travel intention. With the moderation of fear of COVID-19, age had a significantly negative effect on travel intention. The findings confirmed a significant mediating effect of the three dimensions of perceived value and satisfaction on perceived quality and travel intention. fear of COVID-19 had a significant moderating effect on satisfaction and travel intention. In addition, age had a significant negative effect on travel intention under the moderation of fear of COVID-19; thus, travel intention decreases with age.